Student and supervisor perspectives on engaging in collaborative thesis supervision as an online group - Tiffany Williams; Debbie Ryder; Mae Befayed; Ranjani Lata; Shelley Auld (New Zealand Journal of Teachers' Work)
In this text we relfect on an online group supervision within a Master of Education postgraduate programme. Foregrounding the importance of reflexivity (Ortlipp, 2008) four students and their supervisor retrospectively critiqued the online group supervision process they were involved in. Data was collected by each member of the group individually answering six open ended prompts. A reflexive analysis then occurred when the group met and engaged in further candid conversation. From the analysis, the findings showed that the online group supervision process was viewed as a successful practice for the supervisor to share relevant information across the group in a timely and efficient manner. It was also found that the group process provided opportunity for the growth of student expertise as they shared their thesis development amongst their peers in the group. In doing so, a research community began to develop. Whilst the strengths of the group approach to supervision were acknowledged, both the supervisor and students believed that the group supervision approach must also allow for the provision of individual meetings.